اثر الإبتكار على تنافسية المؤسسة الجزائرية - دراسة حالة المؤسسة الوطنية للصناعات الإلكترونية ENIE بسيدي بلعباس - فتان, الطيب; بوصلاح, سفيان; بوشنوف, نوال (Université de M'sila, 2017)
This work deals with innovation impact on enhancing competitiveness of Algerian enterprises ;The National enterprise for Electronic Industries (ENIE) at SidiBel Abbes represents our of investigation area.Through which we tackle the relationship between innovation – in its multiple dimension- and competitiveness. Basic findings include the result that Algerian enterprises should pay attention to changing environment and submerging new data; AS we recommend in this respect, enterprises has to respond intelligently to the opportunities and challenges that lie ahead, by valuing its human capital and innovation as well as modernizing the industrial structure. Also, focusing on research and development is a first step toward building competitive strength.In fact, according to study which concerns about (ENIE) in SidiBelabbes, the Results show an average interest in innovation in its different dimensions, although the scope of its activity strongly needs to strengthen projects innovation that remains an urgent requirement.
Keywords: إبداع ، تنافسية ، تغيير ، بحث وتطوير ، رأس مال بشري ، تطوير تكنولوجي ( innovation, competitiveness, change, research and development, human capital, technological development )